2012
DOI: 10.1074/jbc.m111.331298
|View full text |Cite
|
Sign up to set email alerts
|

p53 Basic C Terminus Regulates p53 Functions through DNA Binding Modulation of Subset of Target Genes

Abstract: Background:The role of the conserved basic C terminus of p53 remains elusive. Results: The C terminus of p53 controls target gene selectivity and is needed for cellular responses. Conclusion: The C terminus of p53 is required for full p53 function. Significance: This provides insight into the basis for target gene selectivity by p53 as well as determination of cell fate outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…In that study the relative ability of WT p53 and p53 in which the last 24 amino acids were deleted (creating Δ24 p53) were compared. It is highly likely that Δ30 p53 and Δ24 p53 are phenotypically equivalent since both lack the full set of C-terminal lysines and previous studies examining either Δ30 p53 (McKinney et al, 2004; Kim et al, 2012) or Δ24 p53 (Hamard et al, 2012) provided virtually identical results i.e. that lack of either 24 or 30 C-terminal amino acids significantly impairs p53 binding and transactivation ability.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In that study the relative ability of WT p53 and p53 in which the last 24 amino acids were deleted (creating Δ24 p53) were compared. It is highly likely that Δ30 p53 and Δ24 p53 are phenotypically equivalent since both lack the full set of C-terminal lysines and previous studies examining either Δ30 p53 (McKinney et al, 2004; Kim et al, 2012) or Δ24 p53 (Hamard et al, 2012) provided virtually identical results i.e. that lack of either 24 or 30 C-terminal amino acids significantly impairs p53 binding and transactivation ability.…”
Section: Resultsmentioning
confidence: 97%
“…To ask if the RE mutation may rescue binding by CTD-deleted p53 in vivo, we took advantage of constructs generated by Hamard et al (Hamard et al, 2012) where the relatively weaker Tp53 gene promoter drives the expression of p53 proteins. In that study the relative ability of WT p53 and p53 in which the last 24 amino acids were deleted (creating Δ24 p53) were compared.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, using cell-based assays where full-length or CTD-deleted p53 proteins were expressed at near physiological levels, Hamard et al . reconfirmed the requirement of the CTD for p53 binding to and transactivation of the promoters of several bona fide p53 targets, such as p21 , Puma , and Mdm2 [48]. Importantly, they also showed that extremely high levels of CTD-deleted p53 transiently overexpressed under the strong human cytomegalovirus promoter may mask the detrimental effect of the CTD absence, emphasizing the need for more-physiological experimental conditions.…”
Section: The Roles Of the P53 Ctd In Dna Bindingmentioning
confidence: 74%